Exploring the association between fat-related traits in chickens and the RGS16 gene: insights from polymorphism and functional validation analysis - Ye, Mao; Fan, Zhexia; Xu, Yuhang; Luan, Kang; Guo, Lijin; Zhang, Siyu; Luo, Qingbin (Frontiers in Veterinary Science, 2023)
Excessive fat deposition in chickens can lead to reduced feed utilization and meat quality, resulting in significant economic losses for the broiler industry. Therefore, reducing fat deposition has become an important breeding objective in addition to achieving high broiler weight, growth rate, and feed conversion efficiency. In our previous studies, we observed high expression of Regulators of G Protein Signaling 16 Gene (RGS16) in high-fat individuals. This led us to speculate that RGS16 might be involved in the process of fat deposition in chickens. Thus, we conducted a polymorphism and functional analysis of the RGS16 gene to investigate its association with fat-related phenotypic traits in chickens. Using a mixed linear model (MLM), this study explored the relationship between RGS16 gene polymorphisms and fat-related traits for the first time. We identified 30 SNPs of RGS16 in a population of Wens Sanhuang chickens, among which 8 SNPs were significantly associated with fat-related traits, including sebum thickness (ST), abdominal fat weight (AFW), and abdominal fat weight (AFR). Furthermore, our findings demonstrated that AFW, AFR, and ST showed significant associations with at least two or more out of the eight identified SNPs of RGS16. We also validated the role of RGS16 in ICP-1 cells through various experimental methods, including RT-qPCR, CCK-8, EdU assays, and oil red O staining. Our functional validation experiments showed that RGS16 was highly expressed in the abdominal adipose tissue of high-fat chickens and played a critical role in the regulation of fat deposition by promoting preadipocyte differentiation and inhibiting their proliferation. Taken together, our findings suggest that RGS16 polymorphisms are associated with fat-related traits in chickens. Moreover, the ectopic expression of RGS16 could inhibit preadipocyte proliferation but promote preadipocyte differentiation. Based on our current findings, we propose that the RGS16 gene could serve as a powerful genetic marker for marker-assisted breeding of chicken fat-related traits.